2004
DOI: 10.3109/2000-1967-109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of haemodialysis and continuous ambulatory peritoneal dialysis on P300 cognitive potentials in uraemic patients

Abstract: The aim of this study was to determine the effects of haemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) on P300 cognitive potentials in patients with chronic renal failure (CRF) and to find out if P300 potential is a valuable marker for following subclinical cognitive disorder.This study was performed in 42 patients with chronic uraemia, of whom 25 were on HD and 17 on CAPD, and in 25 healthy subjects. All the subjects were investigated in terms of P300 cognitive potential obtained from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 10 publications
3
32
1
1
Order By: Relevance
“…Previous investigations of cognitive function among ESRD patients demonstrated that CAPD patient had consistently better cognitive function than HD patients. [14][15][16] In contrast to previous studies, the subjects in this study consisted of patients with ESRD with no clinically evident occurrence of cognitive impairment or dementia. Therefore, cognitive and motor functions were assessed in detail using measures of simple visual discrimination of signal location, short-term memory actualization, simple convergent visual orientation, and convergent thinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations of cognitive function among ESRD patients demonstrated that CAPD patient had consistently better cognitive function than HD patients. [14][15][16] In contrast to previous studies, the subjects in this study consisted of patients with ESRD with no clinically evident occurrence of cognitive impairment or dementia. Therefore, cognitive and motor functions were assessed in detail using measures of simple visual discrimination of signal location, short-term memory actualization, simple convergent visual orientation, and convergent thinking.…”
Section: Discussionmentioning
confidence: 99%
“…Some data suggest that the prevalence of cognitive impairment may be different in patients treated with HD compared with patients treated with CAPD. [14][15][16] They also demonstrated that CAPD patients had consistently better cognitive function than HD patients, but the results from these studies may not reflect the dialysis procedure itself but selection bias as to who is receiving which modality.…”
Section: Introductionmentioning
confidence: 99%
“…18 In patients undergoing peritoneal dialysis, the few available data suggest that the prevalence of cognitive impairment might be lower than in hemodialysis patients. 19,20 However, this apparent discrepancy may reflect selection bias (because the dialysis procedure will depend on the patients' characteristics and thus cognitive function before the introduction of dialysis 21 ) rather than the procedure's characteristics per se.…”
Section: Patients With Stage 5 Ckdmentioning
confidence: 99%
“…ERPs have been used to study the effects of hemodialysis on ESRD patients [13][14][15][16] ; however, many of these previous studies have failed to take into account various co-morbidities (such as coronary artery disease, diabetes mellitus, cerebrovascular disease, anemia, malnutrition etc.) that may contribute to cognitive dysfunction in these patients.…”
Section: Introductionmentioning
confidence: 99%